2021
DOI: 10.1371/journal.pone.0250123
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and vaccine hesitancy: A longitudinal study

Abstract: How do attitudes toward vaccination change over the course of a public health crisis? We report results from a longitudinal survey of United States residents during six months (March 16 –August 16, 2020) of the COVID-19 pandemic. Contrary to past research suggesting that the increased salience of a disease threat should improve attitudes toward vaccines, we observed a decrease in intentions of getting a COVID-19 vaccine when one becomes available. We further found a decline in general vaccine attitudes and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
394
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(444 citation statements)
references
References 39 publications
(36 reference statements)
42
394
5
3
Order By: Relevance
“…These findings might reflect the fact that individuals’ previous positive experiences with influenza vaccines may have resulted in them having more reassuring attitudes towards COVID vaccination. To support this, findings from previous [ 28 , 29 ] and current pandemics [ 43 , 44 , 45 , 46 , 47 , 48 ] showed that regular influenza vaccine takers reported increased risk perception regarding H1N1 influenza, as well as positive attitudes in regard to vaccine safety and the value of vaccination in general.…”
Section: Discussionmentioning
confidence: 92%
“…These findings might reflect the fact that individuals’ previous positive experiences with influenza vaccines may have resulted in them having more reassuring attitudes towards COVID vaccination. To support this, findings from previous [ 28 , 29 ] and current pandemics [ 43 , 44 , 45 , 46 , 47 , 48 ] showed that regular influenza vaccine takers reported increased risk perception regarding H1N1 influenza, as well as positive attitudes in regard to vaccine safety and the value of vaccination in general.…”
Section: Discussionmentioning
confidence: 92%
“…During the first state of emergency, the present research was done when no vaccine was available and little was known about the SARS-COV-2 virus, while the IPSOS survey was conducted in 2021 after the vaccine started to be available for older adults. Attitudes toward vaccination can change throughout a public health crisis ( Fridman et al, 2021 ). Most likely, subsequent scientific information about vaccination benefits and the pro-vaccination national campaign have encouraged vaccination behavior in people with chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…After more than a year into the COVID-19 pandemic, it is clear that age is the most important risk factor for becoming severely ill from the coronavirus. A recent study by Fridman et al (2021) found that individuals with less favorable attitudes toward a COVID-19 vaccination also perceived the virus to be less threatening. As young adults are generally not at risk of becoming severely ill or dying from the virus, they may be less motivated to take the vaccine.…”
Section: The Present Studymentioning
confidence: 99%